Integrated Electrophoresis Separation and Electrochemical Detection in a Paper-based Device. (2017) - González-López, A.; García-Manrique, P.; Blanco-López, M.C.; Fernández-Abedul, M.T.
Abstract: The miniaturization of processes in Analytical Chemistry is a basic trend that has become quite relevant during the last years as well as low-cost methodologies. They offer advantageous characteristics for both, developed and developing countries, with special application to remote sensing, where untrained personnel and power facilities are scarce. Paper-devices have demonstrated their potentiality for this aim with disposable and inexpensive platforms. However, selectivity and sensitivity have to be ensured. In this context, a separation technique (electrophoresis) and a sensitive principle of detection (electrochemistry) are combined. Here we develop a folded paper-based device with integrated electrophoretic separation and electrochemical detection. The platform has different layers with hydrophobic wax barriers that delimit channels for performing both functions. Detection and separation has been demonstrated with epinephrine and hydroquinone analytes.